Mechanics of a rope-braked cycle ergometer flywheel and its use for physiological measurement - Franklin, K. L.; Gordon, R. S.; Baker, J. S.; Davies, B. (Research in Sports Medicine, 2005)
The cycle ergometer is one of the main tools used by physiologists in studies involving the measurement of work or power against physiological criteria. The current mechanical analysis of a Monark 824E rope-braked ergometer is based on a simplified approach. In this study a detailed analysis of the system is adopted to increase understanding. The mechanics of the ergometer flywheel are explained using data generated experimentally and the detailed components of the values of work that comprise the total work done by a subject are discussed. The total work done by a subject in 2.5 minutes at a speed of 60 rpm against a brake mass of 3 kg was 23,034 J compared with the value of 27,000 J that normally would be attributed using the traditional calculations. This 15% difference is mainly due to the incorrect assumption that the brake load is the force due to the basket mass.